Strategi Peningkatan Kapasitas Tampung Reservoir Air Hujan untuk Mengatasi Krisis Air Minum di Desa Jaya - Thamrin Husain; Indra Altarans (Jurnal Karajata Engineering, 2026)
This study aims to develop strategies to enhance the storage capacity of rainwater reservoirs to address the drinking water crisis in Jaya Village. The research employs a qualitative-descriptive and quantitative-applicative approach, focusing on analyzing rainfall data, calculating daily water needs, and designing optimal reservoir dimensions. Data were collected from CHIRPS (Climate Hazards Group InfraRed Precipitation with Station Data), field observations, and interviews with villagers. The results show that the existing reservoir capacity is insufficient to meet water demands during the dry season. Calculations based on extreme rainfall events and household needs indicate that a communal reservoir with a capacity of 54 m³ is required to sustain the village for seven dry months. The proposed reservoir design features a cylindrical shape with a diameter of 4.8 meters and a height of 3 meters, optimized for stability and maintenance. The study highlights the potential of rainwater harvesting as a sustainable solution to water scarcity, emphasizing the integration of technical, social, and environmental considerations. The findings contribute to the development of community-based water management systems adaptable to climate change and local challenges.